PERAMALAN GARIS KEMISKINAN PROVINSI DAERAH ISTIMEWA YOGYAKARTA MENGGUNAKAN METODE DOUBLE EXPONENTIAL SMOOTHING - Adryan Adryan; Shelbi Salsabilla Sururin; Wahyu Sa'dun Akbar; Edy Widodo (LPPM Universitas Bina Bangsa, 2022)
Poverty is the inability to meet the minimum standard of living. This situation can be seen from the low income in meeting basic needs, both in the form of needs for food, clothing, and shelter. Based on Law No. 24 of 2004, poverty is a socioeconomic condition of a person or group of people for which the non-fulfillment of its basic rights to maintain and develop a dignified life. The issuance of this policy from the government is due to differences in social, economic, and natural characteristics and conditions in each region, with the aim of maximizing the potential in each region, so that it is expected to be able to improve welfare and reduce poverty. Yogyakarta Special Region (D.I.Y) is a province-level Special Region in Indonesia located in the southern part of Java Island, and bordering Central Java Province. According to the BPS report, the number of diy poor people until September 2021 was 474.49 thousand people. This study used Double Exponential Smoothing as the analysis method. The results of the analysis obtained are data on the poverty line of the Yogyakarta Special Region from 2004 to 2022 patterned on upward trand. the MAPE value of the model is 1.8% which indicates that the forecasting model uses the DES method accurately. 4. After looking at the comparison plot of the actual data and forecasting. From 2023 to 2027, the poverty line in the Special Region of Yogyakarta will continue to increase compared to the previous year